Formulation of a repellent lotion from essential oils of Alpinia galanga, Citrus grandis and Citrus aurantifolia against mosquitoes Aedes aegypti and Culex quinquefasciatus / Norashiqin Misni - Norashiqin, Misni (2018)
Mosquitoes are one of the deadliest insects in the world. Their ability to carry and spread disease to humans causes millions of deaths every year. The use of mosquito repellent to protect oneself against mosquito bites is now common with plenty of repellent products available in the market. Plant-based repellent products gained much attention among users as they are believed to be safer compared to the synthetic repellent. Unfortunately, most of the plant-based repellent in the market were found to have short protection time and thus most likely to be unreliable to be considered as vector control tools. The development of new repellent formulation that offer longer duration of protection is therefore essential. In this study, in order to obtain the information regarding local plant species that are traditionally used for protection against mosquito bites, 350 questionnaires were distributed among the community in Kota Tinggi District, Johor Malaysia. From the information attained, three plant species were selected to be developed into repellent formulation. The essential oils (EOs) extracted from each plant species were then exposed to a method known to help improve the protection time/repellent effect of the formulation called microencapsulation via interfacial precipitation chemistry technique. Diethyl-m-toluamide (DEET), the synthetic repellent was also exposed to the similar method and used for comparison purpose. Encapsulated EOs and DEET were then formulated into lotion form in order to produce microencapsulated (ME) formulation. The pure active ingredients of EOs and DEET were also formulated using similar procedures to produce iv non-encapsulated (NE) formulation. Both types of formulations were then evaluated for their efficacy against mosquito bites in the laboratory and field conditions. The physical stability of the formulations stored for 12 months at 250C and 400C storage conditions was also assessed. The formulations were further analyzed to determine their preservative capacity against microbe followed by skin irritation and skin sensitization study using rabbit and guinea pig as animal model. Based on the ethnobotanical survey, ten plants species were identified by respondents as being used as mosquito repellent. Three plants species selected for further investigation were C. aurantifolia (leaves), A. galanga (rhizome) and C. grandis (fruit peel). The EOs extracted from these plants was successfully encapsulated with more than 95% encapsulation efficiency were observed for all the microcapsules. ME and NE of EOs and DEET were successfully formulated into lotion form. Efficacy study of the formulation demonstrated that ME formulation of EOs had a remarkable potency as repellent by providing longer duration of protection compared to NE formulations and shown to have comparable effect to repellent available in the market, Citriodiol®-based repellent. This formulation also appeared to demonstrate excellent ability in retaining its physical stability and efficacy over 6 months of storage compared with NE formulations. All formulations presented good preservative capacity against bacteria and fungus. All formulations also indicated absence of skin irritation and sensitization effect upon application on the skin. In conclusion, microencapsulation method used in the development of repellent formulation adds an important dimension in the development of long-lasting protection plant-based repellent formulation against mosquito bites.